Bibelvetenskaplig forskarutbildning i Sverige: Reflektioner med avstamp i Svenska Exegetiska Sällskapets Exegetiska dagar 2022 - Ålöw, Tobias (Svensk exegetisk årsbok, 2023)
Taking the second of SES’ 2022 Exegetical Days as its point of departure, this article discusses the topic of doctoral education in biblical studies in and around Sweden today. In addition to a brief report from the conference, the article first accounts for relevant parts of the governing documents that regulate Swedish postgraduate education. Thereafter, some notable differences that emerge through a comparison of the general syllabi for doctoral studies from the pertinent institutions of higher education (Enskilda Högskolan Stockholm, Gothenburg, Lund, Umeå, and Uppsala University) are highlighted, with a focus on matters related to subject, degree, distribution of credits, as well as usefulness for/collaboration with society. The article points out basic similarities, but also highlights differences and different types of opportunities and risks that might accompany the different programs. In doing so it provides a "snapshot" of doctoral education in biblical studies in Sweden today.